Liquid Chromatography Study on Atenolol-β-Cyclodextrin Inclusion Complex. (1st March 2012) - Buha, Shailesh M.; Baxi, Girin A.; Shrivastav, Pranav S.
Abstract : Inclusion complex formation of atenolol with β -cyclodextrin (β -CD) has been investigated by HPLC on different stationary phases, by varying pH and concentration of β -CD added as an additive in the mobile phase over a wide range of column temperature. Stationary phases of different polarity and hydrophobicity were evaluated to find the best conditions for complex formation. The optimum conditions for inclusion complexation were achieved on YMC ODS-AQ C18 (150 × 4.6  mm, 5 μ) analytical column. The apparent formation constant (K ) of the complex as evaluated by liquid chromatography using retention factors (k ) was 179.47 ± 2.5  M −1 at 25 ° C. The stoichiometry of the complex was 1 : 1 as is evident from the straight line plot of 1/k versus β -CD concentration. The formation of inclusion complex was essentially enthalpy (−42.12 kJ/mol) driven and the binding forces included hydrophobic, van der Waals-London dispersion interactions. The enthalpy-entropy compensation criterion was used to prove the inclusion phenomena.